Strategi Komunikasi Pemasaran dalam Meningkatkan Jumlah Penjualan di PT Bintang Mas Mitra Amanah Medan - Arliansyah Dalimunthe; Putri Mauliza; Aprilda Yanti (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Marketing communication is a tool or medium used by a company or business person to increase the number of visitors. The aim of this research is to explain the marketing communication strategies to enhance sales at PT. Bintang Mas Mitra Amanah. This research utilizes qualitative methods. The data obtained comes from three informants. The data sources used in this study are observation, interviews, and documentation. In this research, data analysis is performed using qualitative methods, starting with reviewing all available data from various sources, namely interviews, observations recorded in notes, and personal documentation, including photographs. The stages in the data analysis process include data reduction, data presentation, and conclusions or verification. The results obtained from this study indicate that marketing communication strategies play a crucial role in the business world, especially in the field of social media. PT. Bintang Mas Mitra Amanah has a significant amount of sales derived from social media. In conclusion, social media plays an important role in the business world.